2019
DOI: 10.1074/jbc.ra119.010324
|View full text |Cite
|
Sign up to set email alerts
|

Genetic code expansion and photocross-linking identify different β-arrestin binding modes to the angiotensin II type 1 receptor

Abstract: The angiotensin II (AngII) type 1 receptor (AT1R) is a member of the G protein–coupled receptor (GPCR) family and binds β-arrestins (β-arrs), which regulate AT1R signaling and trafficking. These processes can be biased by different ligands or mutations in the AGTR1 gene. As for many GPCRs, the exact details for AT1R–β-arr interactions driven by AngII or β-arr–biased ligands remain largely unknown. Here, we used the amber-suppression technology to site-specifically introduce the unnatural amino acid (UAA) p-azi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 55 publications
2
24
0
Order By: Relevance
“…To our knowledge, this was the first experimental evidence documenting an unnatural amino acid replacement in a GPCR expressed in its native environment, and the use of a mutated receptor to photocapture a peptide ligand. Similar UAAR experiments were carried out subsequently on other GPCRs [ 139 , 140 , 141 , 142 ].…”
Section: Genetic Manipulation Of the Receptor Structurementioning
confidence: 78%
“…To our knowledge, this was the first experimental evidence documenting an unnatural amino acid replacement in a GPCR expressed in its native environment, and the use of a mutated receptor to photocapture a peptide ligand. Similar UAAR experiments were carried out subsequently on other GPCRs [ 139 , 140 , 141 , 142 ].…”
Section: Genetic Manipulation Of the Receptor Structurementioning
confidence: 78%
“…The arr-FL of arrestin-1 assumes a helical structure in both the rhodopsin/arr-FL and rhodopsin/arrestin-1 crystal structures, but positioning of this motif differs significantly, suggesting that arrestin-1 may engage the rhodopsin in different conformations. Such conformational plasticity is further supported by a recent study using unnatural amino acid p-azido-L-phenylalanine incorporation into 25 different positions of cytosolic domains of AngII (angiotensin II) type 1 receptor (AT1R) and UV-induced photocross-linking with b-arrestins (122). The study revealed different interaction patterns between b-arrestins and AT1R, suggesting that AT1R/ b-arrestin complexes of different conformations may form.…”
Section: Paradoxical Actions Of B-arrestin As Terminator and Promotermentioning
confidence: 80%
“…Phosphorylation of the C-tail is known to increase b-arrestin affinity for GPCRs (18,32,33). Additionally, molecular and structural studies have established a role for the 8 th helix in enabling both visual arrestin and b-arrestin interactions with GPCRs (19,(34)(35)(36). Both of the motifs investigated in this study have been studied for PAR2 but in different cellular backgrounds (21)(22)(23).…”
Section: Discussionmentioning
confidence: 98%